Pembuatan Web Application untuk Mendukung Pelayanan Asisten Tutor di Universitas Kristen Petra - Kevin Fidelis; Adi Wibowo; Justinus Andjarwirawan (Jurnal Infra, 2017)
Tutor assistant is a term for students who serve new students in small groups, in a coaching program for new students known as Ethics Enrichment. Currently, every support tools that have been used by tutor assistants were printed. In comparison with the number of tutor assistants, the printing of support tools is a waste and not really practical, especially when compared to the advancement of technologies which actually can ease the service of tutor assistants.Web application was made with the purpose of helping tutor assistant service by providing a system that can be accessed across devices and can fulfill the needs of tutor assistants while doing their services. Some features in web application include material access, grade assignment, online attendance form and interactions with new students via sharing or meeting agreement form. Web application also use JSON Web Token to provide login service and email notifications if any content addition occur in web application.After doing some testing, it can be concluded that web application can be accessed nicely across devices. Survey also shows that web application answers the needs in providing a system that support the service of tutor assistants in Petra Christian University, with 59% of respondents agree that the web application is useful and 53% of respondents agree that web application as a whole has been good.